2019
DOI: 10.1186/s12866-019-1449-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic resistance determinants to fusidic acid and chlorhexidine in variably susceptible staphylococci from dogs

Abstract: Background Concern exists that frequent use of topically-applied fusidic acid (FA) and chlorhexidine (CHX) for canine pyoderma is driving clinically relevant resistance, despite rare description of FA and CHX genetic resistance determinants in canine-derived staphylococci. This study aimed to determine minimum inhibitory concentrations (MICs) and investigate presence of putative resistance determinants for FA and CHX in canine-derived methicillin-resistant (MR) and -susceptible (MS) staphylococci.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 68 publications
0
17
1
Order By: Relevance
“…However, more recently, two equine MRSA isolates from Australia were found to harbor qacA/B genes and the study also showed that some MRSA lineages (i.e., ST71) are more likely to carry qac genes ( 47 ). Although in our study carriage of qacA/B was significantly higher in the CoNS-UK isolates compared to the CoNS-RO isolates, Frosini et al ( 45 ) has shown that carriage of the qacA/B gene tends not to correlate with a high chlorhexidine MIC, which brings into question the clinical significance of qacA/B carriage. Nevertheless, the emergence of biocide resistant S. pseudintermedius strains, particularly if concurrently methicillin resistant, would severely limit therapeutic options and potentiate clinical outbreaks as already demonstrated for mupirocin resistance ( 48 ) and chlorhexidine resistance ( 49 ) amongst S. aureus in humans.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…However, more recently, two equine MRSA isolates from Australia were found to harbor qacA/B genes and the study also showed that some MRSA lineages (i.e., ST71) are more likely to carry qac genes ( 47 ). Although in our study carriage of qacA/B was significantly higher in the CoNS-UK isolates compared to the CoNS-RO isolates, Frosini et al ( 45 ) has shown that carriage of the qacA/B gene tends not to correlate with a high chlorhexidine MIC, which brings into question the clinical significance of qacA/B carriage. Nevertheless, the emergence of biocide resistant S. pseudintermedius strains, particularly if concurrently methicillin resistant, would severely limit therapeutic options and potentiate clinical outbreaks as already demonstrated for mupirocin resistance ( 48 ) and chlorhexidine resistance ( 49 ) amongst S. aureus in humans.…”
Section: Discussioncontrasting
confidence: 86%
“…The prevalence of expB and expA genes reported in the current study was lower than the expB prevalence of 23.2% reported in clinical S. pseudintermedius isolates from dogs with superficial pyoderma (27) and the expA gene prevalence of 31% reported in canine S. pseudintermedius isolates from Spain (5). The expA (formerly known as exi) and expB genes encode exfoliating toxins (43) that were shown to be associated with subcorneal clefts, erythema, vesicles, and erosions when purified and injected into canine skin (27,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRSA isolates (CC8 and CC22) represented two clonal complexes found worldwide [ 29 ]. Species and respective resistances were confirmed by PCR following previously described methods [ 30 , 31 ] for species-specific thermonuclease ( nuc ), methicillin-resistance ( mecA ), and presence or absence of tet(M), tet(K), fusB, and fusC .…”
Section: Methodsmentioning
confidence: 99%
“…Donor isolates for FA experiments included two fusB -positive and three fusC -positive MRSP, with resistance genes most likely on transposon-like elements in plasmids ( fusB ) or integrated into the chromosomal DNA in a SCC mec -like cassette ( fusC ). Selection of FA-resistant donors was limited by the infrequent description of these genes in this species [ 30 ]; FA-resistant S. aureus donors were not available for inclusion at the time. Recipient bacteria representing different origins and STs were chosen; all were screened on brain heart infusion agar (BHIA; Oxoid) containing either 30 mg/L tetracycline or 16 mg/L FA to confirm phenotypic susceptibility.…”
Section: Methodsmentioning
confidence: 99%